Local seed shortages addressed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A Kenyan-German seed programme is improving farmers' access to seeds in Kenya's Mwingi District. Poor infrastructure and recurrent seed and food shortages encouraged the German agency for technical cooperation GTZ to introduce a new scheme. Through...